Ready for school: follow the patterns - complete the pictures - Jackson, Shirley; Bandlow, Katja (Ladybird London, 2003)
This is an early learning activity book aimed at improving children's co-ordination and manual dexterity. There is a combination of activities: some involve matching shapes, and others involve completing pictures.